A class of small deviation theorems for Markov chains in bi-infinite random environment. Issue 3 (1st February 2023) - Ding, Chengjun; Liu, Cong; Zang, Qingpei; Niu, Yannan
Abstract: In this article, we mainly study a class of small deviation theorems for Markov chains in bi-infinite random environment. First, we give the definition of Markov chains in bi-infinite random environment. Then, we give some lemmas which are the basis of the main results. Finally, a class of small deviation theorems for Markov chains in bi-infinite random environment is established.